Analysis The Impact of Economic, Population, Agriculture, and Foreign Investment on Deforestation in Indonesia - Farrel Atallah Putra, Muhammad; Gunarto, Toto (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aims to prove several factors, including GRDP per capita, population density, agricultural land, and foreign direct investment (FDI), which are believed to be the causes of deforestation in Indonesia through the analysis of employs panel data covering 32 provinces in Indonesia from 2011 to 2021. The research findings indicate that population density, agricultural land, and FDI have a positive influence on deforestation in Indonesia, while GRDP per capita exhibits a negative correlation. Behind the research findings affirming the factors contributing to deforestation in Indonesia, government policies also play the most significant role in controlling the deforestation trend in Indonesia, either exacerbating or ameliorating the state of forests.